Pears' Cyclopedia: Twenty-Two Complete Works of Reference in One Handy Volume - Herbert C Barratt (UK A & F Pears, Ltd., 1930)
illus Online version: Pear's cyclopedia. London, A. & F. Pears [n.d.] (OCoLC)862084036
General Editor: Herbert C Barratt
Keywords: Encyclopedias (3GdehShYGJs; General